Measuring abnormal brains: building normative rules in Neuroimaging using one-class support vector machines - Joao R Sato; Jane M Rondina; Janaina eMourão-Miranda (Frontiers in Neuroscience, 2012)
Pattern recognition methods have demonstrated to be suitable analyses tools to handle the high dimensionality of neuroimaging data. However, most studies combining neuroimaging with pattern recognition methods focus on two-class classification problems, usually aiming to discriminate patients under a specific condition (e.g., Alzheimer’s disease) from healthy controls. In this perspective paper we highlight the potential of the OC-SVM as an unsupervised or exploratory approach that can be used to create normative rules in a multivariate sense. In contrast with the standard SVM that finds an optimal boundary separating two classes (discriminating boundary), the OC-SVM finds the boundary enclosing a specific class (characteristic boundary). If the OC-SVM is trained with patterns of healthy control subjects, the distance to the boundary can be interpreted as an abnormality score. This score might allow quantification of symptom severity or provide insights about subgroups of patients. We provide an intuitive description of basic concepts in one-class classification, the foundations of OC-SVM, current applications and discuss how this tool can bring new insights to neuroimaging studies.